Static Response of Nanocomposite Electromagnetic Sandwich Plates with Honeycomb Core via a Quasi 3-D Plate Theory - Fatemah H. H. Al Mukahal (Mathematics, 2023)
This article investigates the static analysis of functionally graded electromagnetic nanocomposite sandwich plates reinforced with graphene platelets (GPLs) under hygrothermal loads. The upper and lower layers of nanocomposite face sheets are made of piezoelectromagnetic material with randomly oriented and uniformly disseminated or functionally graded (FG) GPLs throughout the thickness of the layers, while the core layer is made of honeycomb structures. The effective Young’s modulus of the face sheets of the sandwich plate is derived with the aid of the Halpin–Tsai model. While the rule of mixtures is incorporated to compute Poisson’s ratio and electric-magnetic characteristics of the sandwich plate’s upper and lower layers. The governing equations are obtained by a refined quasi-3-D plate theory, with regard to the shear deformation as well as the thickness stretching effect, together with the principle of virtual work. Impacts of the various parameters on the displacements and stresses such as temperature, moisture, GPLs weight fraction, external electric voltage, external magnetic potential, core thickness, geometric shape parameters of plates, and GPLs distribution patterns are all illustrated in detail. From the parameterized studies, it is significant to recognize that the existence of the honeycomb core causes the plate to be more resistant to the thermal condition and the external electric voltage because of the weak electricity and thermal conductivity of the honeycomb cells. Consequently, the central deflection decreases with increasing the thickness of the honeycomb core. Moreover, with varying the external electric and magnetic potentials, the deflection behavior of the sandwich structures can be managed; raising the electric and magnetic parameters contribute to an increment and decrement in the deflection, respectively.